Thulium Laser Resection of Bladder Tumors vs. Conventional Transurethral Resection of Bladder Tumors for Intermediate and High Risk Non-Muscle-Invasive Bladder Cancer Followed by Intravesical BCG Immunotherapy - Liu, Zheng; Long, Gongwei; Zhang, Yucong; Sun, Guoliang; Ouyang, Wei; Wang, Shen; Xu, Hao; Wang, Zhihua; Guan, Wei; Yu, Xiao; Hu, Zhiquan; Chen, Zhong; et al. (Frontiers in Surgery, 2021)
Background: Thulium laser resection of bladder tumors (TmLRBT) is recently considered as a common treatment option for non-muscle-invasive bladder cancers (NMIBC), but whether it is superior to Transurethral resection of bladder tumors (TURBT) are still undetermined. Materials and Methods: We retrospectively screened our institution database to identify patients who were treated by conventional TURBT or TmLRBT for NMIBC and followed by intravesical bacillus Calmette-Guérin (BCG) immunotherapy. The preoperative characteristics, perioperative outcomes, and recurrence-free survival were compared to assess the safety and efficacy of the two procedures. Results: Eventually, 90 patients who underwent TmLRBT (n = 37) or TURBT (n = 53) followed by intravesical BCG immunotherapy were included. Two groups were similar in baseline characteristics except for the smaller tumor size of the TmLRBT group(1.7 cm vs. 2.2 cm; P = 0.036). Obturator nerve reflex occurred in eight patients in the TURBT group and 3 of them suffered from bladder perforation while none happened in the TmLRBT group. The TmLRBT also had a shorter irrigation duration. In the multivariate Cox regression, the TmLRBT was related to less recurrence risk (HR: 0.268; 95% CI, 0.095–0.759; P = 0.013). Conclusion: Our results suggested that TmLRBT is safer than conventional TURBT with fewer perioperative complications, and it offers better cancer control, therefore might be a superior option for NMIBC patients with intermediate and high recurrence risk.